Environmental analysis of structural and technological change in a context of trade expansion: Lessons from the EU enlargement. (March 2021) - Duarte, Rosa; Serrano, Ana
Abstract: The enlargement of the EU towards Central and Eastern Europe started in 2004 and represented a significant challenge for European political and economic agendas. Fifteen years later, Central and Eastern European (CEE) countries have experienced a significant economic growth, mostly based upon industrial development and trade expansion, displaying a strong integration in EU global value chains. In this paper, we aim to analyse if this process of economic and commercial integration has also triggered the externalization of environmental pressures towards Central and Eastern Europe or, on the contrary, trade expansion has been accompanied with a significant technological and structural change in these countries, offsetting the potential scale effects associated to the export growth. To that aim, we use an environmentally extended multi-regional input-output (MRIO) model with information from 2000 to 2016 that will allow us to quantify the PM2.5 emissions embodied in intra-European trade flows. As a second step, we develop a Structural Decomposition Analysis to evaluate the factors driving emissions embodied in exports from CEE to Western EU countries. Highlights: This paper analyses PM2.5 emissions embodied in trade within EU countries. We focus on the relationship between CEE and Western EU economies during 2000–2016. We use multiregional input-output modelling and structural decomposition analysis. Emissions embodied in exports fell, but the trend reversed by 2012. Specialization patterns and efficiency are key to explain the change in emissions.